Early Changes in Patient Access Interval during the COVID-19 Pandemic. (3rd September 2022) - Rollins, Mark K.; Nelson, Alexander R.; Boyd, Jeffrey; Couturier, Katherine; Joseph, Daniel; Burns, Kevin; Cone, David C.
Abstract: Background: COVID-19 was first reported in the United States in January 2020. Its spread throughout the country required EMS systems to rapidly adapt to patient needs while protecting EMS personnel. EMS agencies developed protocols requiring personnel to don enhanced personal protective equipment prior to patient contact. We hypothesized that the Patient Access Interval (PAI), defined as the time from wheels stopped on scene to initial patient contact, had increased during the COVID pandemic. This had the potential to affect patient outcomes, particularly in time-sensitive emergencies such as cardiac arrest or respiratory distress. Methods: This retrospective cohort study used commercial ambulance data from the four largest cities in Connecticut at two different time points: (Pre-COVID) March-May 2019, and (COVID) March-May 2020. PAI was calculated from contemporaneously reported scene times. Total cases were analyzed, and sub-analyses performed for calls located at extended care facilities (ECFs), for all emergent (Echo/Delta) calls, and for medical cardiac arrest calls. Results: 92, 846 total cases were evaluated: 50, 083 from 2019, and 42, 763 from 2020. Cases that did not include necessary time data for PAI were removed, yielding 75, 796 total cases (41, 852 from 2019, 33, 944 from 2020). The average PAI increased from 1 minute 55 seconds (1 m:55s) Pre-COVID to 2 m:18s COVID. ECF PAI increased from 2 m:39s to 3 m:42s. Echo/Delta PAI increased from 1 m:42s to 2 m:07s. Medical cardiac arrest PAI increased from 1 m:27s to 2 m:04s, and ECF cardiac arrest PAI increased from 2 m:18s to 4 m:35s (all comparisons p < 0.01). Conclusions: There were statistically significant increases in all studied PAIs during COVID. The 23 second increase in PAI for all calls may not have been clinically significant in most cases; however, for life-threatening patient presentations, the increase may have been particularly relevant. The increased PAI was compounded in the ECF environment, possibly due to state-mandated screening and temperature checks of EMS personnel before entering facilities. This was highlighted in the ECF cardiac arrest data, which demonstrated a clinically significant increase in PAI of 2m:17s. While this study was limited by the accuracy of contemporaneous time reports by EMS, the results support our hypothesis that PAI had increased during the COVID pandemic.